Qualitative Assessment of Soil and Sediment Pollution with Some Heavy Metals: A Case Study of Duhok Valley in The Kurdistan Region of Iraq - Najlaa Mohammad Ali Qaseem; Maher Khalid; Abdulazeez Al-Saffawi (Science Journal of University of Zakho, 2023)
The current study was conducted on the valley of Duhok and the agricultural lands irrigated from it, where three sites were identified for collecting samples quarterly from soil and sediment using clean plastic bags for the purpose of measuring lead, nickel, cobalt and copper. Pollution load index (PLI), Nemerow pollution index (PIN), Potential Ecological Risk (PER) and Geo-accumulation Index (Igeo) were also calculated according to the internationally approved methods. The results indicated that most of lead, nickel and copper concentrations in soils and sediments exceeded the limits allowed by WHO, reaching annual rates (96.758, 168.746 and 29.88) , (111.25, 219.65 and 48.162) mg.kg-1, respectively. This fluctuation in concentrations was reflected in the values of the studied indicators for both soil and sediment, where 50% and 58% of the studied specimen are of the polluted grade and the remnant are of the non-polluted grade according to the PLI values. So is the case with PIN where 58% of the soil specimen and 41.6% of the sediment samples were of the severe pollution grade, while 25% and 33.3% of the specimen were of the heavy pollution grade and the remnant were slightly pollution grade. The same applies to the results of the PER index values, where 50% and 41.67% of the specimen were from the Medium ecological risk category, and the rest were from the low ecological risk category, likewise for the (Igeo) values, 100% and 96% of the soil and sediment samples were from the Weakly polluted category.